Genotype–phenotype correlation of hereditary erythrocytosis mutations, a single center experience. Issue 8 (16th August 2018) - Oliveira, Jennifer L.; Coon, Lea M.; Frederick, Lori A.; Hein, Molly; Swanson, Kenneth C.; Savedra, Michelle E.; Porter, Tavanna R.; Patnaik, Mrinal M.; Tefferi, Ayalew; Pardanani, Animesh; Grebe, Stefan K.; Viswanatha, David S.; et al.
Abstract : Hereditary erythrocytosis is associated with high oxygen affinity hemoglobin variants (HOAs), 2, 3‐bisphosphoglycerate deficiency and abnormalities in EPOR and the oxygen‐sensing pathway proteins PHD, HIF2α, and VHL. Our laboratory has 40 years of experience with hemoglobin disorder testing and we have characterized HOAs using varied protein and molecular techniques including functional assessment by p50 analysis. In addition, we have more recently commenced adding the assessment of clinically relevant regions of the VHL, BPGM, EPOR, EGLN1 (PHD2), and EPAS1 (HIF2A) genes in a more comprehensive hereditary erythrocytosis panel of tests. Review of our experience confirms a wide spectrum of alterations associated with erythrocytosis which we have correlated with phenotypic and clinical features. Through generic hemoglobinopathy testing, we have identified 762 patients with 81 distinct HOA Hb variants (61 β, 20 α), including 12 that were first identified by our laboratory. Of the 1192 cases received for an evaluation specific for hereditary erythrocytosis, approximately 12% had reportable alterations: 85 pathogenic/likely pathogenic mutations and 58 variants of unknown significance. Many have not been previously reported. Correlation with clinical and phenotypic data supports an algorithmic approach to guide economical evaluation; although, testing is expanded if the suspected causes are negative or of uncertain significance. Clinical features are similar and range from asymptomatic to recurrent headaches, fatigue, restless legs, chest pain, exertional dyspnea and thrombotic episodes. Many patients were chronically phlebotomized with reported relief of symptoms.